PuraStat RADA16 Self-Assembling Peptide Reduces Postoperative Abdominal Adhesion Formation in a Rabbit Cecal Sidewall Injury Model - Gil, Eun Seok; Aleksi, Elton; Spirio, Lisa (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: To evaluate the effect of PuraStat (2.5% RADA16) administration on postoperative abdominal adhesion formation in an in vivo model. Methods: Anesthetized New Zealand white rabbits underwent cecal sidewall abrasion surgery in which the cecal serosa and juxtaposed parietal peritoneum were abraded after access through an abdominal midline incision. Eight animals were randomized to receive PuraStat administration at the interface of the injured tissues before incision closure, and five animals served as untreated controls. Treated animals received 3‒12 mL PuraStat solution per lesion. Animals were sacrificed 14 days after surgery and examined for adhesion formation at the wound site. Results: At study terminus, adhesions were identified in 90% (9/10) of abraded cecum/peritoneal wound sites in untreated controls versus 25% (4/16) of PuraStat-treated sites (p=0.004). Mean±SD Total Adhesion Score (average of the values for extent + strength of the adhesion in both defects per animal; maximum score=14 points) was significantly 76% lower in PuraStat-treated animals (2.0±3.0 points) compared to untreated controls (8.2±1.9 points) (p=0.029). Mean adhesion coverage area of wound sites was 79% lower in PuraStat-treated animals than controls (p<0.001), and mean adhesion durability was 72% lower in PuraStat-treated animals versus controls (p=0.005). Remnant hydrogel was observed at the wound sites of 75% of treated animals at postoperative Day 14. Conclusion: PuraStat treatment has a positive protective effect in the cecal sidewall injury model, and significantly reduces abdominal adhesion formation at the interface of the injured cecum and overlying peritoneal sidewall defect.